An open chat with…Simon Rayner. Issue 2 (17th January 2023) - Tsagakis, Ioannis; Rayner, Simon
Abstract : Simon Rayner joined the FEBS Open Bio Editorial Board in March 2022. Currently, he is Professor of Bioinformatics at Oslo University Hospital and the University of Oslo in Norway. He received a PhD in computational solid‐state physics from the University of East Anglia, in 1991, and served as a Lecturer at the Dept of Physics in the University of Texas before working as a Research Fellow at the McDermott Centre for Human Growth and Development, University of Texas Southwestern Medical Centre at Dallas (UTSW). He went on to become Assistant Professor at the Depts of Biochemistry & Internal Medicine, UTSW before co‐founding BioAutomation Inc. where he developed DNA & RNA synthesis technology and was involved in the Human Genome Project. Simon is a CAS scholar and has also been a Professor of Bioinformatics at the Chinese Agricultural University in Beijing. Here, he tells us about his multi‐disciplinary career transitions, including experience working on three continents, and reflects on implementing open science and fair data. Abstract : Simon Rayner joined the FEBS Open Bio Editorial Board in March 2022. Currently, he is Professor of Bioinformatics at Oslo University Hospital and the University of Oslo in Norway. Here, he tells us about his multi‐disciplinary career transitions, including experience working on three continents, and reflects on implementing open science and fair data.